Metabolic fatigue in resuscitators using personal protection equipment against biological hazard - Francisco Martín Rodríguez (Universidad de Antioquia, 2019)
Objective. To describe the effects of wearing individual protection equipment against biological hazard when performing a simulated resuscitation.